Verizon Lecture: Why Is It So Difficult to Be an Ethical Leader?. (26th July 2018) - Ciulla, Joanne B.
Abstract: In some ways it is more important to understand why it is difficult for leaders to be ethical than it is to understand how to be an ethical leader. By being aware of the common temptations and moral pitfalls of leadership, leaders are better able to avoid them. Like all areas of applied ethics, leadership has its own set of problems that stem from the roles leaders play and their relationship and responsibilities to followers and others. Moreover, leadership is ethically challenging because it and requires control of the self, the ego, and the use of power. This article examines some of the aspects of leadership that make it ethically difficult.